2011
DOI: 10.3109/10929088.2010.542694
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a fluoroscopy-based navigation system enabling a virtual radiation-free preview of X-ray images for placement of cannulated hip screws. A cadaver study

Abstract: BIOMEDICAL PAPEREvaluation of a fluoroscopy-based navigation system enabling a virtual radiation-free preview of X-ray images for placement of cannulated hip screws. A cadaver study Abstract Accurate placement of cannulated screws is essential to ensure fixation of medial femoral neck fractures. The conventional technique may require multiple guide wire passes, and relies heavily on fluoroscopy. A computer-assisted planning and navigation system based on 2D fluoroscopy for guide wire placement in the femoral n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…In clinical use, this may minimise revision surgery caused by early failure of implant fixation in a weakened femoral neck or early osteoarthritis caused by penetration of the femoral head. In comparison to authors who performed biplanar computer-assisted guide wire placement in the femoral neck, the results are similar [13][14][15][16]. In these studies, one of 15 computer-assisted trials required a second pass because the surgeon did not follow the computer plan [14].…”
Section: Drilling Attemptsmentioning
confidence: 61%
“…In clinical use, this may minimise revision surgery caused by early failure of implant fixation in a weakened femoral neck or early osteoarthritis caused by penetration of the femoral head. In comparison to authors who performed biplanar computer-assisted guide wire placement in the femoral neck, the results are similar [13][14][15][16]. In these studies, one of 15 computer-assisted trials required a second pass because the surgeon did not follow the computer plan [14].…”
Section: Drilling Attemptsmentioning
confidence: 61%
“…Our finding of no significant change in task time with AXIS is somewhat different compared with findings for the virtX system (24% decrease) and the zero-dose navigation system (68% increase) (Bott 2008, Müller 2011. Carm positioning accuracy was not reported for these related systems.…”
Section: Discussioncontrasting
confidence: 55%
“…Several groups have tried to address this problem by overlaying artificial X-ray images on a live video feed (Chen 2013, Reaungamornat 2012, Müller 2011. Others have used artificial X-rays for simulation training (Bott 2008, Gong 2014, Cleary 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Navigation has been successfully used in other models, such as fixation of the femoral neck fractures. Studies have demonstrated improved accuracy, precision, better parallelism, and screw spread in the femoral neck with navigation systems . Compared with femoral neck fractures, the deformity present in SCFE poses an additional three‐dimensional challenge, making it a model where navigation may be more useful.…”
Section: Introductionmentioning
confidence: 99%